2019
DOI: 10.1136/bcr-2019-230130
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation ofLegionellapneumonia in a returning traveller

Abstract: A male patient in his mid-60s presented with a severe pneumonia following return to the UK after travel to Crete. He was diagnosed with Legionnaire’s disease (caused by an uncommon serogroup of Legionella pneumophila). He was pancytopenic on admission, and during a long stay on critical care he was diagnosed with a disseminated Aspergillus infection. Bone marrow aspiration revealed an underlying hairy cell leukaemia that undoubtedly contributed to his acute presentation and subsequent invasive fungal infection. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, a comparison of mNGS with traditional microbial diagnostic methods for diagnosing Aspergillus found that mNGS had an accuracy of 78.3%, owing chiefly to the difficulty of extracting nucleic acids from molds, but a specificity as high as 97.5% ( 20 ). A search of PubMed identified only six case reports describing patients with secondary invasive pulmonary Aspergillus infection after Legionella infection ( 21 26 ) ( Table 1 ). Of these six patients, one was diagnosed by autopsy, one by histopathology, and four by microbiological isolation and culture.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a comparison of mNGS with traditional microbial diagnostic methods for diagnosing Aspergillus found that mNGS had an accuracy of 78.3%, owing chiefly to the difficulty of extracting nucleic acids from molds, but a specificity as high as 97.5% ( 20 ). A search of PubMed identified only six case reports describing patients with secondary invasive pulmonary Aspergillus infection after Legionella infection ( 21 26 ) ( Table 1 ). Of these six patients, one was diagnosed by autopsy, one by histopathology, and four by microbiological isolation and culture.…”
Section: Discussionmentioning
confidence: 99%